Clustering Libraries of Compounds into Families: Asymmetry-Based Similarity Measure to Categorize Small Molecules - Samuel, Wieczorek; Samia, Aci; Gilles, Bisson; Mirta, Gordon; Laurence, Lafanechère; Eric, Maréchal; Sylvaine, Roy (IntechOpen, 2011)
None